Nafion® modified with primary amines: chemical structure, sorption properties and pervaporative separation of methanol-dimethyl carbonate mixtures. (February 2018) - Kludský, Miroslav; Vopička, Ondřej; Matějka, Pavel; Hovorka, Štěpán; Friess, Karel
Graphical abstract: Highlights: Ethanolamine-modified Nafion for enhanced membrane separations. FTIR analysis of chemical structure. Characterization of vapour sorption properties. Comparison of three modifying amines: benzylamine, aniline, ethanolamine. Abstract: Nafion®, a highly hydrophilic polymer, is potentially usable for water - organic and hydrophilic organic - hydrophobic organic membrane separations. Since Nafion has accessible sulfo groups in its structure, we propose modifying it with primary amines and did so with aniline, benzylamine and ethanolamine. The resulting modifications contained ionic and sulfonamide bonds, as these were detected using Fourier transform infrared (FTIR) spectrometry. To quantify the separation characteristics of the amine-modified Nafion membranes, vapour sorption microgravimetry and pervaporation experiments were made. The vapour sorption tests showed that amine-modified Nafions sorb ca. 2–4 times less methanol, water and dimethyl carbonate vapours than pure Nafion. Importantly, pervaporation experiments made with methanol-dimethyl carbonate mixtures showed that Nafion modified with ethanolamine is approximately twice as selective to methanol as pure Nafion, the sodium salt of Nafion and Nafion modified with benzylamine.